Effect of Methyl Salicylate (MeSA) induced changes in rice plant (Oryza sativa) that affect growth and development of the rice leaffolder, Cnaphalocrocis medinalis. (January 2018) - Kalaivani, Kandaswamy; Kalaiselvi, Marimuthu Maruthi; Senthil-Nathan, Sengottayan
Abstract: The work was piloted to increase the yield and efficacy of rice farming through introduction of induce defense through Salicylic Acid derivative Methyl Salicylate (MeSA) against rice pest to help the growing world with food security. Induced resistance by MeSA could be an applied tool for the regulation of pests to reduce the broad dependence upon insecticides. The effect of MeSA at 100 mg/L exhibited greater mortality against the rice leaffolder. Growth and development of C. medinalis was directly affected altering rates of ingestion, leaf area damage, stadia weights and development time, pupation, and successful pupation to adults were quantified. Significantly decrease existed experimentally when 75 mg/L of MeSA was applied compared to controls. In both fecundity and hatchability, increased concentrations of MeSA, were correlated with decreased number and success. MeSA influenced nutrition indices negatively in a dose dependent manner. The result showed considerable increase in peroxidase activity of C. medinalis infestation after exogenous application of MeSA treatments. Statistical analysis showed substantial reduction in levels of proteins and lipids in C. medinalis post feeding on MeSA treated rice plants at the highest treatment concentration. The data showed that MeSA affected the gut activities along with reduction in enzyme activities (LDH, ACP, ALP and ATPase). Over all treatment with MeSA resulted in significantly lower survival rates of the rice leaffolder. These results illustrate that MeSA improves the rice resistance to the rice leaffolder through disruption of feeding physiology and may have a significant role in the protection of rice from the pest. Graphical abstract: Highlights: The effect of Methyl Salicylate (MeSA) at 100 mg/L exhibited greater mortality against the rice leaffolder. Leaf area damage, stadia weights and development time, pupation, and successful pupation to adults were affected after treatment with MeSA. Considerable increase in peroxidase, activity of C. medinalis infestation after exogenous application of MeSA treatments in the rice plants. MeSA affected the gut activities along with reduction in enzyme activities (LDH, ACP, ALP and ATPase) of the rice leaffolder.